EFEKTIVITAS PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK PADA PEMBELAJARAN MATEMATIKA - adisty arisma utami (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2023)
Realistic  Mathematics  Education  (PMR)  is  an  approach  to  mathematicseducation  adopted  from  Realistic  Mathematics  Education  (RME)  which  has  beendeveloped  in  the  Netherlands  since  1970.  PMR  tends  to  provide  explanations  related  torealistic  things,  so  that students  can  easily  digest  the  learning  delivered  by  educators  .This  study  aims  to  conduct  a  literature  review  related  to  the  effectiveness  of  realisticmathematics education (PMR) in learning mathematics. The research method chosen inthis study is the SLR (Systematic Literature Review) method. Data collection was carriedout  by  documenting  and  reviewing  all  articles  related  to  mathematics  education  in  theperiod  2010 –2020.  The  articles  used  in  this  study  were  30  accredited  national  andinternational  journal  articles  obtained  from  Google  Schoolar,  Research  Gate,  SINTA,DOAJ,  and  Scopus.  Based  on  this  research,  it  was  found  that  Realistic  MathematicsEducation (PMR) is able to improve learning outcomes and can improve many students'mathematical  abilities.  Starting  from  the  ability  of  intuition,  mathematical  problemsolving ability, connection and communication skills of students.  Keywords: Realistic  Mathematics  Education,  Mathematics  Learning,  Systematicliterature Review